PENGELOLAAN KESAN SELEBGRAM PENGGUNA FITUR INSTAGRAM STORIES DIKALANGAN MAHASISWA KOTA PEKANBARU - Ebroyn.T, Jansen; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research departs from reality where a among students is very enthusiastic in impression management through instagram story features with the perfection of lifestyle that is displayed in order to reach the desired image, In using Instagram stories feature, the student strives to gain sympathy and attention by becoming a figure the ideal in the eyes of his followers. But there is a visible imbalance between the lives of Selebgram who are shown in Instagram stories with real life in the daily lives of the Selebgram. The purpose of this research is to find out how the front stage and the back stage of the user instagram stories feature among students.This reasearch used qualitative methods with a phenomenology approach. The research subjects consisted of three students, which obtained using the Snowball technique. The data collection technique in this research are using the depth interview, observation and documentation, in order to achieve the validity, the author used the participation extension and triangulation.The results showed that the front stage of this impression management by uploading selfie, OOTD or Outfit of the Day activities, endorse, hedonic lifestyle, and communicating in Indonesian mixed with English and tending to use slang and tendencies. Manner or Perception that want to be displayed by the selebgram is the impression of an established and successful adult girl and slang and contemporary style and likes to have friendly and loving nature by many people. While appearance (appearance) The attributes they wear when they live their lives as Selebgram are using make up, wearing branded clothes, using branded bags, branded shoes, using a car and showing a high amount of income or in the form of money. Unlike the front stage, the results of observations on the back stage of celebrity activities are as students and business people. (manner) behavior when they are in their everyday environment, namely expressive girl, simple life and while (appearance) that is without make up, using a negligee, using ordinary T-shirts, using ordinary shorts, using flip flops, using a bicycle motorbikes and cars.Keywords: Impression Management, Selebgram, Instagram stories, Student in Pekanbaru City